From concept to reality: A researcher's journey towards the creation of an industry/education partnership - Bennett, Dawn (Murdoch University, 2004)
The Australian music sector is currently under-researched, inadequately defined, and lacks sector-wide communication. Music is a specialist field that demands exceptional skills and is unlikely to offer rewards commensurate with effort. Rapid change within the industry and related technologies has led to significant revisions in education and training programs. How can continual change be addressed in order to maintain the relevance of these programs? This research sought to establish the potential for a community of practice across the music and education sectors to facilitate the pro-active management of in order to maximise the employment potential of graduates. Whilst the research focused exclusively upon the music industry, it was anticipated that the process and findings would have significant relevance to other disciplines.A lack of primary data resulted in the development if a virtual musician, who undertook tasks such as forming a band and organising a concert. 'Clari' discovered that she had to be multi-skilled in order to remain active within the industry, and she needed access to legal, business, marketing, management and technology expertise. Having established the type of assistance that musicians may require, the research examined ways in which business/education partnerships can best be developed and maintained as positive, rewarding collaborative ventures.The author proposes to describe the experience of partnership establishment, and to share lessons learned in terms of overcoming institutional 'firewalls', establishing networks and dispersing network ownership.